2011
DOI: 10.1063/1.3552533
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Micro Metal Injection Molding By Using Grey Relational Grade

Abstract: Development and characterization of polymers-metallic hot embossing process for manufacturing metallic micro-parts AIP Conf.Abstract. Micro metal injection molding (µMIM) which is a variant of MIM process is a promising method towards near net-shape of metallic micro components of complex geometry. In this paper, µMIM is applied to produce 316L stainless steel micro components. Due to highly stringent characteristic of µMIM properties, the study has been emphasized on optimization of process parameter where Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Ibrahim [15], [16] use Taguchi with Grey relation in optimizing the microMIM process. Chua et al [17] optimizing the injection density and solvent process of parameters using L25 orthogonal array and found that mould temperature and powder loading are the most influential parameters for green part surface quality and injected part strength and density, respectively.…”
Section: ____________________________________mentioning
confidence: 99%
“…Ibrahim [15], [16] use Taguchi with Grey relation in optimizing the microMIM process. Chua et al [17] optimizing the injection density and solvent process of parameters using L25 orthogonal array and found that mould temperature and powder loading are the most influential parameters for green part surface quality and injected part strength and density, respectively.…”
Section: ____________________________________mentioning
confidence: 99%
“…It has been well established as it inherit many features compared to powder compaction such as low production cost at large quantity, good tolerance & mechanical properties, applicable to many materials and ability to sub-micrometer regime [2,3,4]. However there is some limitation in the process such as feedstock preparation, debinding and sintering [3,5]. For this project, High-density Polyethylene will be mixed with nano clay.…”
Section: Introductionmentioning
confidence: 99%
“…For this project, High-density Polyethylene will be mixed with nano clay. Due to the problem of nano powders, optimisation technique has to be implemented in order to reduce defects and give higher shape retention [3]. Here, taguchi method will be implement to estimate the best parameter injection that suites warpage characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization methods alone or integrated with other methods provide very effective techniques in finding the best process parameters values leading to least warpage, shrinkage, distortion and other defect. While in the other hand, it increase the output quality by the contibution percentage [1][2][3]. For this project, High-density Polyethylene will be mixed with natural fibres nano composites which is kenaf.…”
Section: Introductionmentioning
confidence: 99%